Pengaruh Pemberian Penyuluhan terhadap Stigma Penyakit Kusta pada Pasien dan Keluarga Kontak: Suatu Pre - Post Study - Sari, Luh Putu Sustiana Kartika; Karna, N. L. P Ratih Vibriyanti; Rusyati, Luh Made Mas; Karmila, I. G. A. A Dwi; Puspawati, Ni Made Dwi; Winaya, Ketut Kwartantaya (Fakultas Kedokteran Universitas Trisakti, 2025)
Background Stigma toward leprosy patients remains a barrier to efforts to control this disease. Educational interventions are needed to increase public knowledge and reduce prejudice toward patients. This study aims to evaluate the effect of education on leprosy stigma among patients and their family contacts at Prof. Dr. I.G.N.G. Ngoerah General Hospital. Methods This study used a quasi-experimental design with a one-group pretest-posttest approach. The study was conducted at the Dermatology and Venereology Polyclinic of Prof. Dr. I.G.N.G. Ngoerah General Hospital in Denpasar, Bali, from February to July 2025. Data analysis was performed using SPSS version 26.0 at a significance level of α = 0.05. Results A total of 50 respondents were included, comprising 37 leprosy patients and 13 family members. A significant relationship was observed between stigma before and after health education (p = 0.031). Educational level (p = 0.001), clinical presentation (p = 0.002), and economic level (p = 0.029) were also significantly associated with stigma after health education. Respondents with higher education showed a significant decrease in stigma (OR = 11.245; 95% CI: 2.044–61.862; p = 0.005). Similarly, respondents with non-neurological disorders showed lower levels of stigma (OR = 12.415; 95% CI: 2.208–69.808; p = 0.004). Conclusions The findings of this study indicate that health education significantly reduced leprosy-related stigma, with educational level and clinical presentation identified as key determinants.